2016
DOI: 10.2174/1573413712666160530123555
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Atomic Surface Roughness in Nanometric Machining Molecular Dynamics (MD) Simulations

Abstract: Abstract:The concept of atomic surface roughness is very important in the assessment of high performance nano surfaces. The molecular dynamics (MD) simulations were carried out, by using a diamond tool on copper workpiece, for nanomachining. The atomic surface roughness was evaluated after multi-pass runs and these were characterized for various conditions of machined thickness and machining velocity. It was observed that there was no systematic relationship between the depth of cut and the surface roughness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Nano-surface finish, submicron geometric accuracy, and complex machining shapes can be obtained through nano-cutting. [6][7][8][9] For instance, Oluwajobi, AO et al 10 studied the influence of cutting velocity and cutting depth on surface roughness and found that the surface roughness can reach 0.1-0.3 nm by the nanocutting method. Because of its difficult machining characteristics and high cost, the existing experimental methods are no longer the best processing methods for brittle and hard materials like SiC.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-surface finish, submicron geometric accuracy, and complex machining shapes can be obtained through nano-cutting. [6][7][8][9] For instance, Oluwajobi, AO et al 10 studied the influence of cutting velocity and cutting depth on surface roughness and found that the surface roughness can reach 0.1-0.3 nm by the nanocutting method. Because of its difficult machining characteristics and high cost, the existing experimental methods are no longer the best processing methods for brittle and hard materials like SiC.…”
Section: Introductionmentioning
confidence: 99%